Local sources of resilience: Working with social capital - Bernier, Quinn; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2014)
People have always faced shocks and have devised a variety of institutional responses to cope with, recover from, and prevent future impacts. Central to these shocks and this coping capacity, but often underexplored, is the role of social capital. Social capital includes “features of social organization, such as networks, norms, and social trust, that facilitate coordination and cooperation for mutual benefit”1 and can serve as an asset for communities, enabling them to engage in and benefit from collective action and cooperation. While social capital takes many forms, of particular interest here are local‐level organizations and less formal social networks.